Analysis Of Soil Resistance To Liquefaction With Standard Penetration Test - Rifky Arif Aziz Hidayat; Mochammad Irfan; Abdurrachman Aryo Tejo; Ingrid Multi Rezeki (Equivalent: Jurnal Ilmiah Sosial Teknik, 2025)
A phenomenon known as liquefaction occurs when soil loses strength and turns to mud due to earthquake shaking, which can cause damage to infrastructure such as underpass boxes. Based on data from the National Center for Earthquake Studies, Semarang City has a history of earthquakes dating back to 1856 with varying degrees of infrastructure damage. Currently, the phenomenon poses a threat to the people of Semarang City caused by an active fault that runs along the north coast of Central Java. So, this research aims to analyze the soil resistance to liquefaction in the Preliminary Project of Capacity Improvement of Pedestrian Box Underpass Karangingas II Semarang using the Standard Penetration Test (SPT). The data obtained were analyzed using the simplified method proposed by Seed & Idriss (1971). The results show that the soil resistance to liquefaction at a depth of 0 - 4 meters at point BH-02 is quite high, with a safety factor (SF) value greater than 1, so no liquefaction occurs. However, at a depth of 4 - 8 meters, the SF value is less than 1, indicating the liquefaction potential. At points BH-01 and BH-03, the analysis shows the potential for liquefaction at all depths tested. Based on the analysis results, two of the three locations of the box underpass capacity enhancement project have the potential to experience liquefaction, with point two only experiencing liquefaction at a certain depth. Therefore, liquefaction prevention measures are required in these areas.